Amplificação Raman de pulsos curtos em fibras ópticas com ganho periódico - Silva Filho, José Miranda da (2008)
Optical Amplifiers amplify incident light through stimulated emission, the same mechanism which is used by lasers. Indeed, an optical amplifier, it is not but a laser without feedback. Its main ingredient is optical gain which is realized when the amplifier is under pumping process (optically or electrically) in order to cause population inversion at electronic sublevels. In a long run, the optical gain will not only depend on frequency (wavelength) of incident signal, but it also depends on the local beam intensity of the optical gain that is entailed to the amplifier medium. This thesis was stimulated by the continuous pursue of knowledge and understanding of characteristics and phenomena involved in the Raman amplification process in the regime of short pulses which would be relevant as the appliance for processes in which such phenomena can not be neglected. Without loss of generality, we considered the case of where there is an only one channel to another one by the fact that the gain and the refractive index both depend on the number of channels. In this thesis, it has also been simulated the optical amplification where the gain was constant in order to comparing to the periodic gain presented in this thesis. In addition, the effects of dispersion, self phase modulation, pulse walk-off, Raman effects and pulse depletion were considered as important factors for Raman amplification of short pulses. That was also considered for our simulations a weak CW signal or a Raman seed to be amplified by an intense pump Gaussian pulse. All the simulations were achieved using a well-known spectral numerical method namely Split-Step Fourier Method for solving the coupled Nonlinear Schrödinger Equations.